2017
DOI: 10.1017/thg.2017.37
|View full text |Cite
|
Sign up to set email alerts
|

Holocene Selection for Variants Associated With General Cognitive Ability: Comparing Ancient and Modern Genomes

Abstract: Human populations living during the Holocene underwent considerable microevolutionary change. It has been theorized that the transition of Holocene populations into agrarianism and urbanization brought about culture-gene co-evolution that favored via directional selection genetic variants associated with higher general cognitive ability (GCA). To examine whether GCA might have risen during the Holocene, we compare a sample of 99 ancient Eurasian genomes (ranging from 4.56 to 1.21 kyr BP) with a sample of 503 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 58 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…If recent selection favored IQ-promoting variants and purged IQ-reducing variants, the more recent polymorphisms will be IQ-promoting, which will result in bias in favor of the discovery population. There is some evidence of an increase in PGS over time [97]. Of course, the reverse would be true, if recent selection disfavored high IQ alleles.…”
Section: Cognitive Ability and Education-related Polygenic Scores (Edmentioning
confidence: 99%
“…If recent selection favored IQ-promoting variants and purged IQ-reducing variants, the more recent polymorphisms will be IQ-promoting, which will result in bias in favor of the discovery population. There is some evidence of an increase in PGS over time [97]. Of course, the reverse would be true, if recent selection disfavored high IQ alleles.…”
Section: Cognitive Ability and Education-related Polygenic Scores (Edmentioning
confidence: 99%
“…The study of highly polygenic selection via changes in frequencies of many alleles (soft sweeps) in humans has advanced recently due to the availability of large-scale, powerful computer clusters and large genomic datasets. A number of recent studies based on genomic data have found evidence of recent polygenic selection in humans over time [29,30] and space [31][32][33][34]. These findings indicate selection for, e.g., height [31], body mass [32], cognitive ability [33], educational attainment [34,35], and schizophrenia [36].…”
Section: Genomic Studies Of Selection In Humansmentioning
confidence: 99%
“…Furthermore, it has been shown that the Neanderthal admixture % in modern Eurasians has been decreasing over time, consistent with polygenic selection against whatever traits Neanderthal ancestry has higher polygenic scores for (Gregory et al, 2017;Simonti et al, 2016). Especially notable among the studies mentioned is that some of them found evidence of recent selection for educational attainment (Beauchamp, 2016;Kong et al, 2017;Woodley et al, 2017), which is highly genetically correlated with cognitive ability and often used as a proxy in genomic studies (Hill, Davies, McIntosh, Gale, & Deary, 2017;Marioni et al, 2014;Rietveld et al, 2014;Zabaneh et al, 2017). Taken together, these facts suggest the possibility that selection for cognitive ability has not been equal for all groups in recent history (e.g.…”
Section: Genomic Studies Selection In Humansmentioning
confidence: 92%
“…Despite this, soft sweeps are considered by some researchers to be the dominant mode of adaptation in humans (Schrider & Kern, 2017). A number of recent studies based on genomic data have found evidence of recent polygenic selection in humans (Berg, Zhang, & Coop, 2017;Joshi et al, 2015;Mathieson et al, 2015;Woodley, Younuskunju, Balan, & Piffer, 2017), including selection that differed by population such that populations would, over time, acquire different average polygenic scores for the traits (Berg et al, 2017;Joshi et al, 2015;Piffer, 2015;Robinson et al, 2015;Turchin et al, 2012). One example of this is the study by Robinsen et al (2015), which examined differences in height and BMI among 14 European national populations and found that some of the observed national differences in height and 5 A variety of times are used for this trait including skin color, skin tone, skin brightness, skin lightness.…”
Section: Genomic Studies Selection In Humansmentioning
confidence: 99%